CHALLENGES AND SOLUTIONS IN TEACHING COUNTRY STUDIES TEXTS TO ACADEMIC LYCEUM STUDENTS - Kayumova Muyassar Urinbayevna (World Scientific Research Journal, 2025)
Abstract. Teaching country studies texts in academic lyceums presents unique challenges, particularly in non-native English-speaking contexts. This study explores the difficulties encountered by students when reading country studies texts and proposes solutions to enhance comprehension and engagement. The research involved 12 students from Group 16 at the MIA Namangan Academic Lyceum. A mixed-methods approach was used, incorporating pre-tests, post-tests, surveys, and classroom observations. The findings reveal key barriers such as unfamiliar vocabulary, cultural differences, and limited reading strategies. Solutions include the use of visual aids, contextualized learning, and interactive teaching methods. The study provides practical recommendations for improving the effectiveness of country studies instruction in academic lyceums.